2015
DOI: 10.5114/aoms.2015.52359
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-490-5p is a novel tumor suppressor targeting c-FOS in human bladder cancer

Abstract: IntroductionRecent studies have demonstrated the critical roles of micro-RNAs in tumorigenesis and tumor progression. Here, we describe the regulation and function of miR-490-5p in bladder cancer.Material and methodsPaired tissue samples were collected from bladder cancer patients (n = 20). Real-time PCR revealed that miR-490-5p expression was significantly down-regulated in human bladder cancer tissues and cells. Also there was an inverse relationship between the expression level of miR-490-5p and the patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 31 publications
3
32
1
Order By: Relevance
“…For example, miR-490-5p serves as a suppressor in renal cell carcinoma with a significant decrease in the expression level and its inhibitory effect can be reversed by exogenous PIK3CA [29]. Besides, researchers also found that the expression of miR-490-5p frequently decreased in the HCC tissue samples and cells as a novel tumor suppressor by directly targeting c-FOS [31]. Meanwhile, the anti-oncogenic role of miR-490-5p has been verified for its suppressive impacts on bladder cancer carcinogenesis [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, miR-490-5p serves as a suppressor in renal cell carcinoma with a significant decrease in the expression level and its inhibitory effect can be reversed by exogenous PIK3CA [29]. Besides, researchers also found that the expression of miR-490-5p frequently decreased in the HCC tissue samples and cells as a novel tumor suppressor by directly targeting c-FOS [31]. Meanwhile, the anti-oncogenic role of miR-490-5p has been verified for its suppressive impacts on bladder cancer carcinogenesis [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR-490-5p is dramatically downregulated in several forms of human cancer including renal cancer, colorectal cancer, and bladder cancer [29,30,31]. For example, miR-490-5p serves as a suppressor in renal cell carcinoma with a significant decrease in the expression level and its inhibitory effect can be reversed by exogenous PIK3CA [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-time PCR revealed that miR-490-5p expression was significantly down-regulated in human bladder cancer tissues and cells, compared to normal adjacent bladder tissues and non-malignant bladder cell lines [30][31][32]. There was also an inverse correlation between the level of miR-490-5p and the pathological grade of bladder cancer [30].…”
Section: Discussionmentioning
confidence: 96%
“…MicroRNAs are a class of small non-coding RNAs, which possess various functions involving the regulation of apoptosis, proliferation, and autophagy [3][4][5][6]. MiR-26b (gene ID: 31612) belongs to the miR-26 fam-ily.…”
Section: Introductionmentioning
confidence: 99%